Biodiesel in Holy Quran: Among The Review of The Arabic Lexicography and Modern Science - Saipolbarin , Ramli; Sumaiya, Zainal Abidin; Ahmad Fikri, Husin
The Holy Qur’an is a miracle revealed to Prophet Muhammad, Sallallahu Alayhi Wa Salam, that not only discusses elements on beliefs but at the same time, it is compact with some absolutely amazing scientific facts. There are many verses that discuss the description of the scientific facts in the holy Quran. Among the scientific facts found in the holy Quran is the verse that deals with the concept of energy sources such as biodiesel which is found in Yas eenverse 80. However, the interpretation of this verse according to academicians of the past has been from a different perspective. Findings in the biodiesel field by modern scientists have opened a new chapter in the interpretation related to the biodiesel concept found in the holy Qur’an. This study will analyze the opinion of the Arab-Islamic scholars in the interpretation of this verse from the perspective of Islamic code and Arabic lexicography. Furthermore, this discussion will be conducted to examine the relationship of this verse with the concept of biodiesel from the perspective of modern science. The results of the experiments that have been conducted showing that the am ount of energy that results from the reaction of plants, solvents and catalysts to produce biodiesel which is one of the potential of alternative energy sources to replace conventional fuels. The formation of the chemical structure of biodiesel produced from the breakdown of triglyceride structure ( i.e oil from gree plants) that reacts with hydroxide ions and produce three molecules of fatty acid methyl esters FAME(i.e biodiesel ) and one molecule of glycerol . It shows that green elements found in plant s is an energy element . It is hoped that this study will open up new perspectives on the interpretation of the verse that relates to the concept of biodiesel in holy Quran based on scientific facts. Indirectly, it also proves that the holy Quran is the revelation of God and not the invention of Prophet Muhammad.